2015
DOI: 10.1039/c5ra07923c
|View full text |Cite
|
Sign up to set email alerts
|

An amorphous barium titanate thin film improves light trapping in Si solar cells

Abstract: A new anti-reflection coating based on amorphous barium titanate (a-BTO) was developed using RF magnetron sputtering technique. Systematic studies on the structural and optical properties were carried on a-BTO thin films deposited on polished Si and textured Si substrates. In the visible range of solar spectrum, the refractive index was found to be 2.02-1.91 with high transmittance of greater than 85 %. Maximum reduction in the reflectance for a-BTO on polished Si and texture Si substrates was found to be 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Among the contenders, perovskite BaTiO 3 (BTO), as a typical lead‐free displacement‐type ferroelectric featuring a large dielectric constant, stands out . Many researchers have investigated the functionalities of BTO thin film deposited on Si substrates, which not only can be used as a gate insulator, but also has other properties such as a rectifying effect, a photovoltaic effect, a room temperature luminescent effect, and an antireflection effect …”
Section: Introductionmentioning
confidence: 99%
“…Among the contenders, perovskite BaTiO 3 (BTO), as a typical lead‐free displacement‐type ferroelectric featuring a large dielectric constant, stands out . Many researchers have investigated the functionalities of BTO thin film deposited on Si substrates, which not only can be used as a gate insulator, but also has other properties such as a rectifying effect, a photovoltaic effect, a room temperature luminescent effect, and an antireflection effect …”
Section: Introductionmentioning
confidence: 99%
“…for antireflection. Perovskite titanium oxides have already been reported to operate as effective AR single layer coatings for silicon solar cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…BTO thin films are distinguished by broad UV Vis transparency and relatively high refractive index > 2.0 (589 nm) [6,24,25]. Therefore similarly to well-known high-refractive index oxides, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, porous SiO 2 is preferred due to reasonably low refractive index (n < 1.45) with good environmental stability and durability. Recently, authors have demonstrated improvement in light trapping in Si solar cells with maximum reduction in reflection by 85-100% in visible region of 400-550 nm when amorphous BaTiO 3 thin film with refractive index of 2.02-1.91 were deposited over Si solar cells [4]. However, single layer anti-reflection coating can minimize reflections at one specific wavelength typically at normal incidence which limits its use for broad visible range.…”
Section: Introductionmentioning
confidence: 99%